2021
DOI: 10.1111/ppa.13515
|View full text |Cite
|
Sign up to set email alerts
|

Cassava common mosaic virus infection affects growth and yield components of cassava plants (Manihot esculenta) in Argentina

Abstract: Cassava is an important crop with great economic and social significance in many countries. Most of its biomass is usable: storage roots can be destined for industry or fresh consumption, leaves are a source of protein, vitamins, and minerals, and stems can be used as propagation material. Due to its vegetative propagation, cassava yield is greatly constrained by viral diseases. Cassava common mosaic virus (CsCMV), one of the most widely spread viruses in Latin America, is the only cassava‐infecting potexvirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…In fact, dry matter in CFSD-affected roots diminished by 5.73% and 10.88% in Valencia and Señorita, respectively [33], and by 4.76% and 5.84% in BRA383 and Reina. A reduced dry matter accumulation is related to a reduced starch yield and has already been reported in relation to virus infections in cassava by other groups [39,40]. Among the organic acids, malic and succinic acids showed a significant increase in CFSD-affected roots in the four genotypes evaluated.…”
Section: Cfsd Affects the Yield And Sugar Content Of Rootssupporting
confidence: 68%
See 2 more Smart Citations
“…In fact, dry matter in CFSD-affected roots diminished by 5.73% and 10.88% in Valencia and Señorita, respectively [33], and by 4.76% and 5.84% in BRA383 and Reina. A reduced dry matter accumulation is related to a reduced starch yield and has already been reported in relation to virus infections in cassava by other groups [39,40]. Among the organic acids, malic and succinic acids showed a significant increase in CFSD-affected roots in the four genotypes evaluated.…”
Section: Cfsd Affects the Yield And Sugar Content Of Rootssupporting
confidence: 68%
“…infections in cassava by other groups [39,40]. Among the organic acids, malic and succinic acids showed a significant increase in CFSD-affected roots in the four genotypes evaluated.…”
Section: Cfsd Affects the Yield And Sugar Content Of Rootsmentioning
confidence: 84%
See 1 more Smart Citation
“…Además, esta manera de trabajar hizo y sigue haciendo propicia la ejecución de proyectos de investigación y la formación de recursos humanos calificados mediante el desarrollo de estadías, pasantías, tesinas de grado o tesis de posgrado (Mroginski et Scocchi, 1992;Scocchi et al, 1996;Medina et al, 2007a;Cavallero, 2010;Medina, 2010;Bertollo et al, 2015;Galeano, 2016;Schaller, 2016;Medina et al, 2017b;Bertollo, 2019;Zahner, 2021). Estas herramientas académicas o de interacción inter-institucionales, favorecieron el aumento del número de las entradas, haciendo posible la preservación de un patrimonio natural invaluable, útil para el progreso productivo y económico de la región y para el desarrollo de estudios científicos relacionados con aspectos morfogénicos, sanitarios, genéticos, agronómicos y tecnológicos (Medina et al, 2003;Medina et al, 2007b;Cavallero et al, 2012;Zanini et al, 2018;Collavino et al, 2022).…”
Section: Resultados Y Discusiónunclassified
“…CsCMV causes mosaic leaf symptoms and leaf blade distortion, especially in young leaves; these symptoms lead to progressive loss of chloroplast function and diversion of carbon flux in source leaves (Zanini et al, 2021). In turn, recent studies have shown that CsCMV infections affect parameters involved in yield components, namely plant height, shoot fresh weight, fresh weight of tuberous roots, tuberous root number, fresh weight of individual tuberous roots, total fresh weight per plant, estimated yield of tuberous root, tuberous root diameter and tuberous root length, causing important reductions in plant growth and tuberous root production and quality (Collavino et al, 2022). On the other hand, although CsCMV has no known biological vector (Adams et al, 2004), it infects host tissues easily and can persist in the propagation material and in work tools, which contributes to its great dispersal (Silva et al, 2011;Zanini et al, 2018).…”
Section: Evidence Of Cassava Common Mosaic Virus In Cassava Shoot Api...mentioning
confidence: 99%